Different Global Journalisms
XVI, 205 p.
Keywords: This edited collection seeks to better understand how journalism across cultures differs, presenting an in-depth exploration of global practices that departs from the typical Western-centric approach. Journalists across the world are trained, generally speaking, within Western models of reporting and are taught to do so as a practice where reporters need to aspire and aim for. Yet what such training is short of achieving is teaching reporters how to 'do' journalism within their own environments. In turn, what is required is a method of journalistic training and practice that is reflective of the actual practice reporters encounter on the ground. In order to do so, a better understanding of how journalism is practised in different parts of the world, the context surrounding such practices, the issues and challenges associated, and the positive practices that Western journalism can offer, is necessary. Promoting and deploying a culturally-specific and politically-relevant journalism, this book provides just that. Saba Bebawi is Professor of Journalism at the University of Technology Sydney, Australia. She has published on media power and the role of media in democracy-building, in addition to investigative journalism in conflict and post-conflict regions. Oxana Onilov is a social researcher with a PhD in communication and media studies from the University of Technology Sydney. She has worked as a researcher on various topics, including the role of social media in protest participation, health communication and measurement and evaluation of communication. .